A Public Security Approach to Peru’s Economic Reactivation - Zanabria Cabrera, Luis Carlo (2023)
This paper examines the structural challenges resulting from the COVID-19 pandemic and its impact on Peru's economic reactivation. We analyze archetypal problems in Peruvian society that have persisted since pre-pandemic times, including informality, urban lawlessness, and negative perceptions of security among citizens. These challenges significantly influence public policies and reflect broader socio-cultural issues that hinder economic reactivation. We explore alternative approaches to traditional obstacles deterring economic growth, emphasizing the crucial role of public security policies in promoting a balanced economic reactivation strategy at the national level. Citizens' protection and security in their daily urban activities are essential to enhancing economic interactions in cities. We also highlight the need to reconsider governmental ideology when planning public security policies, which often discriminate against social classes and stigmatize certain areas without a solid rationale to support such actions.